Konsep Ishlah Dalam Al-Qur’an (Studi Tematik Tafsir Jami Li Ahkam Al-Qur’an) - Fitria Anisatun Nahdliyah (PT. Hasba Edukasi Mandiri, 2025)
This study explores the concept of Islah in the Qur'an with a thematic study approach based on Tafsir Al-Qurthubi. Islah, which generally means reparation, peace or reconciliation, is one of the central concepts in Islamic teachings that involves efforts to improve the circumstances of individuals, society, and social relations. Through the analysis of the verses of the Qur'an related to Islah and the interpretation given by Al-Qurthubi, this study found that Islah has a wide dimension, covering moral, social, and spiritual aspects. The Tafsir of Al-Qurthubi shows that Islah does not only mean repairing physical damage, but also repairing moral and spiritual damage in humans and society. This concept is also emphasized as an obligation for every Muslim individual, both in a personal and social context. The results of this study show that Islah in the Qur'an is the foundation for the creation of a harmonious and peaceful life, as well as a means to get closer to Allah SWT.